Naskah Akademik: Inkonsistensi Peraturan Dan Keterlibatan Pendidikan Tinggi - Alfaris, Muhammad Ramadhana (Universitas Widya Gama Malang, 2024)
The purpose of this research is to determine the form of unclear norms in the preparation of academic texts, and to determine the involvement of universities through academic texts in the formation of regional regulations. The method used in this research uses normative legal research methods which raise the theme of legal systematics or the systematics of statutory regulations with vertical and horizontal levels of synchronization, with legal, conceptual, historical, theoretical and interpretive approaches. The results of this research show that explanatory words or adverbs, and/or academic texts have very different positions so that their diction cannot be in harmony because each position is very different. Apart from that, there are inconsistencies in norms which cause laws and regulations to be out of sync with each other, so that there is no normative harmonization from a vertical and/or horizontal perspective. Meanwhile, higher education institutions' involvement in academic texts is still situationally involuntary, namely a temporary situation within the limits of academic paper preparation activities and there is no aspect of continuity of this involvement. Thus, the position of academic texts is very respectable, however, in terms of legal norms governing academic texts, they are still not clear, so there is no legal certainty.